Deceptive Advertising with Rational Buyers - Piccolo, Salvatore; Tedeschi, Piero; Ursino, Giovanni (Management Science, 2018)
We study a simple game in which two sellers supply goods whose quality cannot be assessed by consumers even after consumption but can be verified with some probability by a public authority. Sellers may induce a prospective buyer into a bad purchase through comparative deceptive advertising. The central contribution of this paper is the characterization of a class of pooling equilibria in which low-quality sellers deceive a buyer who is Bayes-rational and makes a purchase decision on the basis of the available information. The analysis of these equilibria suggests that high-quality firms should pursue more intensive advertising campaigns than their low-quality competitors. Surprisingly, we find conditions under which sellers’ expected profit is higher in pooling equilibria than in the separating equilibrium in which quality is reflected by prices and there is no need to waste resources in advertising. Hence, we show that there are plausible cases in which firms should be ex ante willing to tolerate some degree of deceptive advertising by low-quality competitors. In addition, although in these equilibria the buyer purchases low-quality goods with positive probability, the expected utility can be higher than in a separating equilibrium in which the buyer purchases the high-quality good for sure. In this sense, the model also offers an argument in favor of a lenient regulatory approach to deceptive advertising. The online appendix is available at https://doi.org/10.1287/mnsc.2016.2665 . This paper was accepted by J. Miguel Villas-Boas, marketing.